Els estudis filològics universitaris al País Valencià - Casanova, Emili (Caplletra. Revista Internacional de Filologia, 2015)
Abstract: Brief comments on the doctorate thesis and dissertations read in the Universitites of Valencia from 1982 to 1986, which dealt with any aspect of Catalan Philology or any topics related to it.